DOT1L: a key target in normal chromatin remodelling and in mixed-lineage leukaemia treatment. Issue 5 (3rd May 2020) - Sarno, Federica; Nebbioso, Angela; Altucci, Lucia
ABSTRACT: Methylation of histone 3 at lysine 79 (H3K79) is one of the principal mechanisms involved in gene expression. The histone methyltransferase DOT1L, which mono-, di- and trimethylates H3K79 using S-adenosyl-L-methionine as a co-factor, is involved in cell development, cell cycle progression, and DNA damage repair. However, changes in normal expression levels of this enzyme are found in prostate, breast, and ovarian cancer. High levels of H3K79me are also detected in acute myeloid leukaemia patients bearing MLL rearrangements (MLL-r). MLL translocations are found in approximately 80% of paediatric patients, leading to poor prognosis. DOT1L is recruited on DNA and induces hyperexpression of HOXA9 and MEIS1 . Based on these findings, selective drugs have been developed to induce apoptosis in MLL-r leukaemia cells by specifically inhibiting DOT1L. The most potent DOT1L inhibitor pinometostat has been investigated in Phase I clinical trials for treatment of paediatric and adult patients with MLL -driven leukaemia, showing promising results.